The Motivational Landscape of Indonesian ESP Students - Rochmawan, Muhammad Rizky; Fitria Wahyu Nugraheni (Journal of Educational Review and Cultural Studies, 2023)
Recognizing the critical role of motivation in language learning, this mixed-methods study explored the primary sources of motivation among Indonesian ESP students and their impact on engagement, aiming to inform effective instructional practices. The research revealed a strong positive correlation between motivation and engagement. Intrinsic motivation, rooted in enjoyment, interest, and personal relevance, emerged as a particularly powerful predictor of active participation, consistent effort, and proactive learning behaviours. The study also highlighted the importance of supportive teachers and a positive learning environment in cultivating intrinsic motivation. These findings underscore the need for ESP educators to prioritize strategies that tap into students’ inherent interests, provide opportunities for autonomy and competence, and foster a sense of relevance and connection to the subject matter. By creating a more motivating learning environment, ESP instructors can empower students to achieve their language learning goals and succeed in their chosen fields.